Neural Signatures of Handgrip Fatigue in Type 1 Diabetic Men and Women - Tyagi, Oshin; Zhu, Yibo; Johnson, Connor; Mehta, Ranjana K.; Sasangohar, Farzan; Erraguntla, Madhav; Qaraqe, Khalid (Frontiers in Human Neuroscience, 2020)
Type 1 diabetes (T1D) is associated with reduced muscular strength and greater muscle fatigability. Along with changes in muscular mechanisms, T1D is also linked to structural changes in the brain. However, the central mechanisms of fatigue with T1D, and associated sex differences, remain unknown. The aim of this study was to determine the impact of handgrip fatigue in T1D males and females and examine T1D-related differences in neural activation and functional connectivity patterns. Forty two adults, balanced by T1D status (control vs T1D) and sex (male vs female), performed submaximal isometric handgrip contractions until voluntary exhaustion. Initial strength, endurance time, strength loss, force variability and complexity measures, and hemodynamic responses from motor-function related cortical regions, using functional near-infrared spectroscopy (fNIRS), were obtained. Females exhibited lower initial strength, shorter endurance times, and greater strength loss than males. While initial strength was significantly lower in the T1D group compared to their counterparts, endurance times and strength loss were comparable between the two groups. Force complexity was found to be lower throughout the experiment for the T1D group, indicating lower online motor adaptability. Despite similar fatigue levels, T1D adults exhibited increased neural activation in the left and right supplementary motor areas (SMA) over time. A Sex × Condition × Fatigue interaction effect showed that while increased activation was observed in both T1D females and healthy males from the Early to Middle phase, this was not observed in healthy females or T1D males. These findings demonstrate the importance of examining both neural and motor performance signatures when investigating the impact of chronic conditions on neuromuscular fatigue. Additionally, the findings have implications for developing intervention strategies for training, rehabilitation, and ergonomics considerations for individuals with chronic conditions.